A Retrospective & Descriptive Study Of Fatal Electrocution Autopsies At A Tertiary Care Center (2022–2024) - Biswal, Jagajyoti; Ranjan Dash, Saumya; Das, Sudeepa; Maniarasan, N (Journal of Forensic Medicine and Toxicology, 2026)
Electrocution is a significant but under-monitored public health concern in low- and middle-income countries. This  retrospective descriptive study analyzed 60 fatal electrocution autopsies performed at a tertiary care hospital between  2022 and 2024. Cases were selected through purposive sampling based on predefined inclusion criteria. Data included  victim demographics, seasonal variations, voltage source, manner of death, and characteristic autopsy findings. Young  adult males constituted 92% of victims, with most deaths occurring during summer and monsoon seasons. Low-voltage  household electricity accounted for two-thirds of cases. Characteristic external findings included dermo-epidermal  burns (75%), entry–exit wounds (48%), and crocodile-skin patterned arc lesions (13%). Nearly all deaths (98%) were  accidental. The study highlights the preventable nature of electrocution fatalities and the urgent need for improved  domestic electrical safety, infrastructural regulation, and seasonal public health interventions
Keywords: Electrocution; Forensic autopsy; Electrical injuries; Injury epidemiology